2012
DOI: 10.1186/1471-2458-12-404
|View full text |Cite
|
Sign up to set email alerts
|

Cluster-randomised trial to evaluate the ‘Change for Life’ mass media/ social marketing campaign in the UK

Abstract: BackgroundSocial marketing campaigns offer a promising approach to the prevention of childhood obesity. Change4Life (C4L) is a national obesity prevention campaign in England. It included mass media coverage aiming to reframe obesity into a health issue relevant to all and provided the opportunity for parents to complete a brief questionnaire (‘How are the Kids’) and receive personalised feedback about their children’s eating and activity. Print and online C4L resources were available with guidance about healt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
82
1
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 96 publications
(90 citation statements)
references
References 29 publications
6
82
1
1
Order By: Relevance
“…It is notable that a national social marketing campaign (Change4Life, [40]) was in its early stages when this study was undertaken, and may not yet have had chance to take effect. Data published since has shown that Change4Life has improved knowledge and awareness of PA in parents of mixed ethnicities, but this does not necessarily translate to changes in behaviour [41].…”
Section: Discussionmentioning
confidence: 99%
“…It is notable that a national social marketing campaign (Change4Life, [40]) was in its early stages when this study was undertaken, and may not yet have had chance to take effect. Data published since has shown that Change4Life has improved knowledge and awareness of PA in parents of mixed ethnicities, but this does not necessarily translate to changes in behaviour [41].…”
Section: Discussionmentioning
confidence: 99%
“…A recent review found a small effect of community-wide physical activity interventions on physical activity levels in low-SES groups, however again the evidence base was limited (Cleland et al, 2012b). Similarly, a recent evaluation of the 'Change for Life' public health campaign in the UK found little benefit of the intervention on physical activity and dietary behaviours, although engaging with the intervention had a positive impact on low-SES families and a negative impact on high-SES families (Croker et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Recent research suggests young adults view health promotion messages as unpopular and lack concern for future health (Poobalan et al, 2012). An evaluation of the UK-based 'Change for Life' public health intervention revealed a common perception among people from all SES backgrounds that their existing eating and physical activity behaviours were satisfactory, with the cost of healthier eating seen as a barrier among low-SES families (Croker et al, 2012). Awareness of the impact of financial status on family food choices has also been documented among primary school children (Fairbrother et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…It is anticipated that there may be a low response rate and response bias towards parents who are more interested and engaged in their child’s health [13]. To address these issues the questionnaire will be distributed to all parents of children enrolled in the NCMP and a number of reminders and incentives will be used.…”
Section: Discussionmentioning
confidence: 99%